ANALISIS KEMAMPUAN PEMECAHAN MASALAH SISWA SMK DITINJAU DARI DISPOSISI MATEMATIS - Yuni Hajar; Veny Triyana Andika Sari (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2018)
The purpose of this study was to analyze the difficulties faced by Vocational High School students in working on problem solving test that were reviewed based on students' mathematical disposition. The research method used is descriptive analysis method to analyze available and processed data to obtain a clear picture of the facts and the relationship between the phenomena studied. The sample in this study was Vocational High School student class XI Accounting in Cimahi. The result of this study base on. students' mathematical disposition is students have difficulties in almost every indicator of problem solving ability. This is caused by several factors such as students who are not used to facing problem solving test. Efforts can be made to overcome student difficulties, such as using innovative learning approaches and media.